Multimodal investigation of fMRI and fNIRS derived breath hold BOLD signals with an expanded balloon model. - Emir, U; Ozturk, C; Akin, A (2008)
Multimodal investigation of blood oxygenation level-dependent (BOLD) signals, using both functional near-infrared spectroscopy (fNIRS) and functional magnetic resonance imaging (fMRI), may give further insight to the underlying physiological principles and the detailed transient dynamics of the vascular response. Utilizing a breath hold task (BHT), we measured deoxy-hemoglobin (HbR) and oxy-hemoglobin (HbO) changes via fNIRS and blood oxygen level dependent (BOLD) changes by fMRI. Measurements were taken in four volunteers asynchronously and carefully aligned for comparative analysis. In order to describe the main stimulus in BHT, partial pressure of carbon dioxide (PaCO(2)) parameter was integrated into the balloon model as the driving function of cerebral blood flow (CBF) which led to the development of an expanded balloon model (EBM). During BHT, the increase in HbR was observed later than the BOLD peak and coincided temporally with its post-stimulus undershoot. Further investigation of these transients with a PaCO(2) integrated balloon model suggests that post-stimulus undershoot measured by fMRI is dominated by slow return of cerebral blood volume (CBV). This was confirmed by fNIRS measurements. In addition, the BOLD signal decreased with the increase of the initial level of PaCO(2) derived from EBM, indicating an effect of basal CBF level on the BOLD signal. In conclusion, a multimodal approach with an appropriate biophysical model gave a comprehensive description of the hemodynamic response during BHT.